Pathways from inability to blamelessness in moral judgment. (18th August 2022) - Turri, John
ABSTRACT: This paper evaluates opposing theories of the relationship between inability and blamelessness in commonsense morality. One theory (the prevention account) is inspired by the "ought implies can" principle in philosophy. On this account, whenever an agent is unable to perform an action, she is blameless for not performing it because she is not obligated to perform it. In other words, blamelessness is explained by the absence of obligation, which in turn is explained by inability. An alternative theory (the exculpation account) is inspired by recent psychological findings. On this account, sometimes when an agent is unable to perform an action, she has a moral obligation to perform it but is blameless for not doing so because she has a legitimate excuse. In other words, blamelessness is explained by a legitimate excuse for an unfulfilled moral obligation, and inability explains the excuse. The results from three experiments undermine the prevention account and support the exculpation account. These results advance our understanding of moral judgment and contribute to ongoing debates in moral philosophy and psychology.